Study on Equilibrium Distribution Coefficients during Osmotic Dehydration of White Gourd Slices. Issue 3 (25th February 2014) - Fan, Kai; Chen, Libing; Du, Kun; Yan, Fengwei
Abstract Equilibrium distribution coefficients were obtained to understand osmotic dehydration mechanism and to optimize and control osmotic dehydration process. The equilibrium distribution coefficients of white gourd slices were determined during osmotic dehydration at different temperatures (30–50C) and maltose syrup concentrations (40–60%, w/w). Equilibrium distribution coefficients as a function of temperature and maltose syrup concentration were modeled using nine nonlinear models. The results showed that the equilibrium distribution coefficients of water and solids ranged from 0.3411 to 0.8406 g/g and from 1.2392 to 1.5754 g/g, respectively. The best models for the equilibrium distribution coefficients of water and solids are, respectively, λse = −0.8345 + 0.0281T + 6.5665C − 0.0627CT + 0.0001T2 − 4.9081C2 + 0.0004T2C2 [R2 = 0.9899, sum of squared error (SSE) = 2.0511 × 10−4, root mean square error (RMSE) = 0.0143, χ2 = 9.2299 × 10−4, P = 2.10%], λse = −0.8345 + 0.0281T + 6.5665C − 0.0627CT + 0.0001T2 − 4.9081C2 + 0.0004T2C2 (R2 = 0.9734, SSE = 3.0827 × 10−4, RMSE = 0.0176, χ2 = 0.0014, P = 1.09%). Practical Applications Osmotic dehydration of white gourd slices in maltose syrup solution was investigated experimentally in different solution concentrations and at different temperatures. The equilibrium distribution coefficients of water and solids were calculated during osmotic dehydration of white gourd in maltose syrup solution. The equilibrium distribution coefficients of water and solids for white gourd slices as a function of maltose syrup concentration and temperature were investigated.